2021
DOI: 10.3390/life11121353
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pediatric Nutrition as a Modifiable Risk Factor for Precocious Puberty

Abstract: Puberty is a critical phase of growth and development characterized by a complex process regulated by the neuroendocrine system. Precocious puberty (PP) is defined as the appearance of physical and hormonal signs of pubertal development at an earlier age than is considered normal. The timing of puberty has important public health, clinical, and social implications. In fact, it is crucial in psychological and physical development and can impact future health. Nutritional status is considered as one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 245 publications
(431 reference statements)
0
15
0
Order By: Relevance
“…Leptin is a cytokine produced mainly by adipocytes, which acts as an anorectic factor, playing an essential role in controlling body weight, food intake, and energy balance by inhibiting the hypothalamic neuropeptide Y (NPY), thus suppressing appetite (13,14). Normal body weight and composition must be attained during childhood to avoid pubertal dysfunction (1). In addition to the leptin-NPY interaction, some studies showed that leptin acts on puberty and reproductive function by directly interacting with the KiSS-1gene.…”
Section: Physiology Of the Pubertymentioning
confidence: 99%
See 3 more Smart Citations
“…Leptin is a cytokine produced mainly by adipocytes, which acts as an anorectic factor, playing an essential role in controlling body weight, food intake, and energy balance by inhibiting the hypothalamic neuropeptide Y (NPY), thus suppressing appetite (13,14). Normal body weight and composition must be attained during childhood to avoid pubertal dysfunction (1). In addition to the leptin-NPY interaction, some studies showed that leptin acts on puberty and reproductive function by directly interacting with the KiSS-1gene.…”
Section: Physiology Of the Pubertymentioning
confidence: 99%
“…Puberty is a complex process with wide physiological variation. Mechanisms regulating the onset of puberty involve genetic, nutritional and environmental interactions (1).…”
Section: Precocious Pubertymentioning
confidence: 99%
See 2 more Smart Citations
“…Genes partly determine when an individual’s puberty begins. For instance, makorin ring finger protein 3 ( MKRN3 ) and delta-like noncanonical Notch ligand 1 ( DLK1 ) are key genetic drivers in the progression of central precocious puberty [ 7 , 8 ]. Obesity also plays a critical role [ 9 ].…”
Section: Introductionmentioning
confidence: 99%